(untitled) (Research, Society and Development, 2021)
Objective: To analyze the profile of oral health attention offered to children and adolescents in Primary Care and the factors that influence the integrality of care for these users. Methodology: 68 dental surgeons from João Pessoa/PB were interviewed and information was collected from the National Program for Improving Access and Quality in Primary Care, 1st cycle. The data were submitted to the Chi-square and Fisher’s exact tests (p-value≤0.05). Results: It was found that 63.2% of professionals refer patients in cases of urgency in primary dentition and 52.9% point out problems in referral and counter-referral, with children’s non-collaboration being the greatest difficulty mentioned (25.4%). Most Basic Health Units had adequate structural and environmental characteristics and availability of equipment, materials and supplies. Differences were identified between Health Districts regarding Basic Health Units with difficulties in assistance. Conclusion: There are weaknesses that can compromise the implementation of the principle of integrality and they are differentiated in the Health Districts.